Knowledge, attitude and self-efficacy program intended to improve public health professionals' ability to identify and manage perinatal depressive symptoms: a quasi-experimental study - Nitikorn Phoosuwan; Pranee C. Lundberg (BMC, 2020)
Abstract Background During the perinatal period women lack screening and treatments for perinatal depressive symptoms, while public health professionals (PHPs) in primary care centres (PCCs) need training for identification and management of such symptoms. This quasi-experimental study was aimed at evaluating knowledge, attitudes and self-efficacy among PHPs after participating in a Knowledge, Attitude, and Self-efficacy (KAS) program for identification and management of perinatal depressive symptoms. Method The KAS-program, carried through in Sakonnakhon in north-eastern Thailand, comprised one day of theory and a four-week period of field practice. Thirty-three PHPs from PCCs participated in the program. Twenty-three of them participated in focus group discussions (FGDs). Chi-square for trend, paired-sample T-tests and content analysis were used. Results Knowledge, attitude and self-efficacy scores increased after the PHPs had fully participated in the KAS-program. Four categories emerged from the FGDs: increased understanding and knowledge, being aware and having a positive attitude, having confidence and ability to work, and need of regular training and feedback. Conclusion The KAS-program may contribute to giving PHPs in PCCs the knowledge, positive attitude and self-efficacy they need to identify and manage perinatal depressive symptoms. Implementation of the KAS-program to other healthcare professionals such as nurses/midwives is great of interest.